Plexiform Neurofibroma of the Larynx in Children: About an Unusual Case Report - R Mahdoufi; I Barhmi; N Tazi; R Sami; R Abada; M Roubal; M Mahtar (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Introduction: The plexiform neurofibroma is a rare benign tumor which is often associated to type 1 neurofibromatosis or Von Recklinghausen's disease. The laryngeal involvement in neurofibromatosis is extremely rare.  The objective of our report is the consideration of laryngeal neurofibromatosis in the differential diagnosis of dyspnea in infants and children.  Summary of the clinical case: We report the case of a 4 year-old child who presented with inspiratory dyspnea. Laryngoscopy revealed a mass obstructing completely the laryngeal vestibule. Pathological examination of the resected tissue revealed a plexiform neurofibroma after immunohistochemical examination. The patient had regular follow up and she remained symptom free.   Discussion: There is an association between neurofibromatosis type 1 and plexiform neurofibromas of the larynx. Analysis of the margins of neurofibromas of the larynx associated with neurofibromatosis type 1 may  elp predict clinical behavior.